2020
DOI: 10.1093/cercor/bhaa291
|View full text |Cite
|
Sign up to set email alerts
|

Knock-Down of Hippocampal DISC1 in Immune-Challenged Mice Impairs the Prefrontal–Hippocampal Coupling and the Cognitive Performance Throughout Development

Abstract: Disrupted-in-schizophrenia 1 (DISC1) gene represents an intracellular hub of developmental processes. When combined with early environmental stressors, such as maternal immune activation, but not in the absence of thereof, whole-brain DISC1 knock-down leads to memory and executive deficits as result of impaired prefrontal–hippocampal communication throughout development. While synaptic dysfunction in neonatal prefrontal cortex (PFC) has been recently identified as one source of abnormal long-range coupling, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 72 publications
3
12
0
Order By: Relevance
“…In line with previous studies 25 , 27 , 28 , firing and coupling deficits at pre-juvenile age might reflect abnormal circuit wiring initiated at earlier stages of development. To test this hypothesis, we investigated the activity patterns within entorhinal-hippocampal-prefrontal networks in neonatal (P8-10) CON ( n = 14) and GE ( n = 14) mice (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In line with previous studies 25 , 27 , 28 , firing and coupling deficits at pre-juvenile age might reflect abnormal circuit wiring initiated at earlier stages of development. To test this hypothesis, we investigated the activity patterns within entorhinal-hippocampal-prefrontal networks in neonatal (P8-10) CON ( n = 14) and GE ( n = 14) mice (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Taken together, these results indicate that already at pre-juvenile age the LEC-dependent associative recognition memory is impaired in GE mice. This cognitive deficit complements the previously reported poor performance in other non-associative recognition tasks 25 , 27 , 28 .…”
Section: Resultssupporting
confidence: 87%
“…Three mechanisms might cause these early deficits: (1) local disruption of prefrontal circuits, (2) local disruption of hippocampal circuits, and/or (3) abnormal long-range communication between PFC and HP. We previously confirmed the first two mechanisms and reported that (1) layer 2/3 pyramidal neurons in PFC experienced excessive microglia-induced synaptic pruning leading to impaired β-γ oscillations ( Chini et al, 2020 ) and (2) the sharp-waves, firing, and network activity in hippocampal CA1 area are decreased in GE mice ( Xu et al, 2021 ). Here, we address the third hypothesis and investigate the long-range connectivity between HP and PFC throughout development in dual-hit GE mice.…”
Section: Introductionmentioning
confidence: 63%
“…We previously showed that these deficits emerge already early in life, at a developmental stage corresponding to neonatal period in mice (first postnatal week) and third gestational trimester in humans ( Clancy et al, 2001 ). Dual-hit GE mice mimicking both the genetic [mutation of the intracellular hub of developmental processes disrupted-in-schizophrenia 1 (DISC1) gene; Brandon and Sawa, 2011 ] and the environmental [challenge by maternal immune activation (MIA)] background that has been related to mental illness, have abnormal patterns of early electrical activity both in PFC and HP ( Hartung et al, 2016 ; Xu et al, 2019 , 2021 ; Chini et al, 2020 ). Additionally, prefrontal-hippocampal coupling through synchrony of oscillatory activity as well as directed HP-to-PFC interactions are diminished.…”
Section: Introductionmentioning
confidence: 99%
“…In several developmental mouse models of mental disorders, b -g prefrontal oscillations are impaired from the first few postnatal days until adulthood (Xu et al, 2019;Chini et al, 2020;Xu et al, 2020). Severely simplified dendritic arborization, as well as decreased spine density and firing rate of L2/3 pyramidal cells underlie these abnormalities.…”
Section: Developmental Miswiring As Disease Substratementioning
confidence: 99%